A study on the formation of the high-Tc superconducting phase of Bi1.6Pbo4Sr2Ca2Cu3Oy as determined by the melt quenched precursors - Penaranda, Phebe M. (Animo Repository, 1997)
The melt quenched method is applied in the fabrication of Bi1.6Pb0.4Sr2Ca2Cu3Oy superconducting ceramics. The samples were prepared as determined by its stoichiometric composition by melting it at 1080 degrees Centigrade for five minutes. The melts were poured immediately onto a stainless steel plate and quenched to room temperature. The samples were ground, pelletized and annealed at a constant temperature of 840 degrees Centigrade for 24 hours. Three trials were made to verify the results. The effects of melting the lead doped BSCCO were investigated using SEM/EDAX, DTA, XRD and X-T analyses. The superconducting phase appeared even in the as-quenched samples. Glass forming tendency is also remarkably retarded. Annealing at 840 degrees Centigrade for 24 hours completely vanished this glass forming ability. XRD results showed the coexistence of the low Tc, high Tc and several non superconducting phases. EDAX results show several impurity phases that inhibit the formation of the 2212 and 2223 phases. DTA results show that a decrease in the endothermic peak intensity suggest a slower nucleaction and an increase in the grain size of the sample. This is consistent with the SEM results. Tc onset was strongly dependent on the amount of non superconducting impurities, grain size and intensity of the endothermic peak that affects the phase formation in the partially melted state.